Bacterial biofilms in the human body: prevalence and impacts on health and disease - Perry, Elena K.; Tan, Man-Wah (Frontiers in Cellular and Infection Microbiology, 2023)
Bacterial biofilms can be found in most environments on our planet, and the human body is no exception. Consisting of microbial cells encased in a matrix of extracellular polymers, biofilms enable bacteria to sequester themselves in favorable niches, while also increasing their ability to resist numerous stresses and survive under hostile circumstances. In recent decades, biofilms have increasingly been recognized as a major contributor to the pathogenesis of chronic infections. However, biofilms also occur in or on certain tissues in healthy individuals, and their constituent species are not restricted to canonical pathogens. In this review, we discuss the evidence for where, when, and what types of biofilms occur in the human body, as well as the diverse ways in which they can impact host health under homeostatic and dysbiotic states.